Perspectives on the metabolism of strigolactone rhizospheric signals - Wang, Jian You; Braguy, Justine; Chen, Guan-Ting Erica; Jamil, Muhammad; Balakrishna, Aparna; Berqdar, Lamis; Al-Babili, Salim (Frontiers in Plant Science, 2022)
Strigolactones (SLs) are a plant hormone regulating different processes in plant development and adjusting plant’s architecture to nutrition availability. Moreover, SLs are released by plants to communicate with beneficial fungi in the rhizosphere where they are, however, abused as chemical cues inducing seed germination of root parasitic weeds, e.g. Striga spp., and guiding them towards host plants in their vicinity. Based on their structure, SLs are divided into canonical and non-canonical SLs. In this perspective, we describe the metabolism of root-released SLs and SL pattern in rice max1-900 mutants, which are affected in the biosynthesis of canonical SLs, and show their accumulation of two putative non-canonical SLs, CL+30 and oxo-CL (CL+14). Using max1-900 and SL-deficient d17 rice mutants, we further investigated the metabolism of non-canonical SLs their possible biological roles. Our results show that the presence and further metabolism of canonical and non-canonical SLs are of particular importance for their role as Striga seed germination stimulants rhizospheric interactions. In conclusion, our data indicate that the root-released SLs are mainly responsible for rhizospheric communications and have low impact on plant architecture, which makes targeted manipulation of root-released SLs an option for rhizospheric engineering.